GE_GERICHTE P/3656/2017 vom 2. Mai 2022 - GE Cour de justice (2022)
CLASSEMENT DE LA PROCÉDURE;RECEL;PRESCRIPTION;DÉCISION NON FORMELLE;MISE EN ACCUSATION;ORDONNANCE PÉNALE;INDEMNITÉ(EN GÉNÉRAL);PRÉSOMPTION D'INNOCENCE;SÉQUESTRE(MESURE PROVISIONNELLE);ATTRIBUTION(SENS GÉNÉRAL);POSSESSION | CPP.329; CPP.267; CPP.257; CPP.426